Urban retail systems: vulnerability, resilience and sustainability. Introduction to the Special Issue - Barata-Salgueiro, Teresa (2021)
Contemporary urbanization process threatens our environment, challenges the livability of cities, their ability to build localized competitive advantages, to attract investment, to create jobs and ensure the well-being of people in a sustainable development path. However, in recent years, several experiences from both communities and public policy on governance, mobility or in the supply system of goods and services can be seen as signs of change in how we are dealing with urban problems. The need for sustainable transformation of cities is reinforced by the 2030 Agenda for Sustainable Development [1], particularly Sustainable Development Goal 11, which is dedicated to making cities inclusive, safe, resilient and sustainable. It is likely that cities will be greener and healthier, built around a more sustainable paradigm, which will be characterized by compactness and polycentrism, regeneration of the built environment instead of sprawl, walkability and soft forms of mobility, new combinations of scales of activity (from physical proximity to online presence) and more intense use of digital technologies embedded across all city functions.